АБЕРАНТНЕ МЕТИЛЮВАННЯ АСОЦІЙОВАНИХ З РАКОМ ГЕНІВ У ХВОРИХ НА РАК МОЛОЧНОЇ ЗАЛОЗИ З В’ЄТНАМУ: ЗВ’ЯЗОК З КЛІНІКО-ПАТОЛОГІЧНИМИ ОСОБЛИВОСТЯМИ - Dieu Vuong, Linh; Ngoc Nguyen, Quang (PH Akademperiodyka, 2023)
Background. Epigenetic alteration is one of the most common molecular changes identified in the progression of breast cancer (BC). Aim. To study the frequency and relation between methylation of BRCA1, MLH1, MGMT, GSTP1, APC, RASSF1A, p16, WIF, and EGFR and the clinicopathological features in Vietnamese BC patients. Materials and Methods. Methylation-specific polymerase chain reaction (MS-PCR) and SPSS 20.0 software were utilized in order to identify methylated frequency as well as evaluate its relationship with the patient’s clinical features. Results. In 162 BC cases, the methylation rates of the selected genes were 53.7%, 22.8%, 38.9%, 34.6%, 29.0%, 46.3%, 20.4%, 18.5%, and 28.4% respectively. In 32 cases of benign breast diseases (BBD) – 12.5%, 15.6%, 6.3%, 3.1%, 12.5%, 21.9%, 3.1%, 15.6% and 3.1%. BC samples displayed higher BRCA1, MGMT, GSTP1, APC, RASSF1A, WIF1, and p16 methylation levels than BBD samples (p < 0.001). Hypermethylation of BRCA1, GSTP1, and RASSF1A was predominant in the invasive ductal carcinoma, while hypermethylation of BRCA1, GSTP1, RASSF1A, WIF-1, and p16 was found to significantly correlate with lymph node metastasis (p < 0.05). Hypermethylation of BRCA1, MGMT, and GSTP1 was more common in stage III (p < 0.05) than in stages I/II, whereas MLH1 methylation was predominant in stage I and APC methylation was less common in stage III (p = 0.03). In addition, methylation of RASSF1A and EGFR was more frequent in younger patients (p < 0.01) than in elder patients. Conclusion. These data suggest that a gene panel (BRCA1/MGMT/GSTP1) can be used to support the diagnosis and screening of Vietnamese patients’ BC with a sensitivity of 70%, and a specificity of 85%.